Shapeshifters, Time Travellers and Storytellers - Hopkins, Candice; Swanson, Kerry (Royal Ontario Museum, 2008)
"Incorporating evocative objects from the Museum's collections, this thought-provoking exhibition presents eight contemporary Aboriginal artists whose works explore the ways in which past and present continue to merge and shape one another. This exhibition features eight striking installations, including more than 25 individual artworks by internationally renowned artists Suvinai Ahsoona, Faye HeavyShield, Cheryl L’Hirondelle, Isuma Productions (Zacharias Kunuk and Norman Cohn), Brian Jungen, Alan Michelson, Nadia Myre and Kent Monkman. Five of the eight works, which include video, sound, sculpture, drawings, painting and performance art, were created specifically for this exhibition. Co-organized by the Royal Ontario Museum’s Institute for Contemporary Culture and the imagineNATIVE Film + Media Arts Festival. Co-curated by Kerry Swanson and Candice Hopkins.
Section: 59 p. : ill. (chiefly col.), ports. ; 19 x 23 cm.
Keywords: _Nettoyé